2019
DOI: 10.1111/vcp.12721
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytosis and Histoplasma‐like fungal infection in 32 cats

Abstract: Histoplasmosis is one of the most common systemic fungal diseases in cats from the United States. It commonly causes respiratory or disseminated disease and is often associated with one or more cytopenias. Here, we describe 32 cats in which a Histoplasma‐like fungal infection was associated with concurrent hemophagia in at least one sample site, commonly spleen, bone marrow, liver, and/or lymph node. The degree of hemophagia was characterized as moderate or marked in the majority of cases, and in all cases, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, increased hemophagocytic macrophages in bone marrow were not observed in this cat. Hemophagocytic syndrome is rarely diagnosed in cats, with only three case reports and one retrospective study reported in the literature to date 6–9 . Hemophagocytosis was observed in the bone marrow examinations of three case reports and 9 of 10 cats with histoplasmosis 6–9 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, increased hemophagocytic macrophages in bone marrow were not observed in this cat. Hemophagocytic syndrome is rarely diagnosed in cats, with only three case reports and one retrospective study reported in the literature to date 6–9 . Hemophagocytosis was observed in the bone marrow examinations of three case reports and 9 of 10 cats with histoplasmosis 6–9 .…”
Section: Discussionmentioning
confidence: 98%
“…Hemophagocytic syndrome is rarely diagnosed in cats, with only three case reports and one retrospective study reported in the literature to date 6–9 . Hemophagocytosis was observed in the bone marrow examinations of three case reports and 9 of 10 cats with histoplasmosis 6–9 . In humans, bone marrow hemophagocytosis was observed in approximately half of the patients diagnosed with HLH, and the absolute numbers of hemophagocytosis were low 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several, but not all, reports of canine and feline patients with hemophagocytic syndrome also document non-regenerative anemia as well. [4][5][6] It is possible that phagocytosis of erythroid precursors contributed to the nonregenerative nature of the anemia in this case, but it is possible other mechanisms were also involved. Given the lack of dysplastic changes in the erythroid lineage and no history of heavy metal exposure or heat stroke, the rubricytosis was most likely secondary to hypoxic bone marrow damage secondary to the marked anemia.…”
Section: Hemophagocytic Syndrome (Hemophagocytic Lymphohistiocytosis)mentioning
confidence: 94%
“…Several case reports in dogs have used similar criteria as in human cases, including bi-or pancytopenia and hemophagocytic macrophages in the bone marrow or spleen; the proportion of hemophagocytic macrophages required for diagnosis varied from >2% to >5%. [4][5][6][7] In this case, the presumptive diagnosis of hemophagocytic syndrome was based on bicytopenia and the presence of increased numbers of hemophagocytic macrophages in the spleen and bone marrow. Histiocytic sarcoma was ruled out based on the percentage of macrophages being <30% of the nucleated cells.…”
Section: Hemophagocytic Syndrome (Hemophagocytic Lymphohistiocytosis)mentioning
confidence: 94%